2013
DOI: 10.12968/denu.2013.40.9.711
|View full text |Cite
|
Sign up to set email alerts
|

Special care dentistry: part 2. dental management of patients with drug-related acquired bleeding disorders

Abstract: Being able to recognize which drugs may cause bleeding problems at an early stage will lead to good patient management, particularly in planning and delivering treatment following invasive procedures such as dental extractions. Whilst most patients can be successfully treated in general dental practice, the clinician may need to make a decision on whether or not to refer a patient to specialist services for all dental treatment, or to share care between primary care and specialist services for selected procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
(6 reference statements)
0
17
0
1
Order By: Relevance
“…If dental extraction is essential, full blood count should be checked, as the patient might need a blood transfusion to raise the platelets and hemoglobin level, antibiotic and/or G‐CSF to raise the neutrophil count. Timing of dental procedure is crucial as the lifespan of platelets is 7 to 10 days, while the lifespan of leucocyte is 4 weeks . Patients taking Azacitidin (Vidaza ® , Celgene ® ) have this once daily for 7 days followed by a rest period of 21 days (for a minimum of six cycles).…”
Section: Discussionmentioning
confidence: 99%
“…If dental extraction is essential, full blood count should be checked, as the patient might need a blood transfusion to raise the platelets and hemoglobin level, antibiotic and/or G‐CSF to raise the neutrophil count. Timing of dental procedure is crucial as the lifespan of platelets is 7 to 10 days, while the lifespan of leucocyte is 4 weeks . Patients taking Azacitidin (Vidaza ® , Celgene ® ) have this once daily for 7 days followed by a rest period of 21 days (for a minimum of six cycles).…”
Section: Discussionmentioning
confidence: 99%
“…During blood vessel injury, hemostasis relies on interactions between the vascular vessel wall and activated platelets as well as clotting factors (De et al, 2013).Any marked defect at one of these stages results in bleeding disorders. Vascular wall defects, platelet defects, or deficiency of clotting factors can affect the severity level of bleeding episodes (Nizarali & Rafique, 2013). Thus; patients may have gentle, moderate, or severe episodes of bleeding.…”
Section: Dental Management Of Patients With Inherited Bleeding Disordersmentioning
confidence: 99%
“…Gingko biloba is a substance widely used by the population around the world in the form of gel and capsules to treat vascular disorders 18 , aid cognitive development 14 , prevent dementia 12 and Alzheimer's disease 10 , and treat macular degeneration, tinnitus and erectile 10 . Its antiplatelet action has already been reported [1][2][3][4][5] , although there are controversies on this matter 22 .…”
Section: Ginkgo Biloba (Gingko Biloba)mentioning
confidence: 99%
“…Several medicinal properties have been reported, such as antimicrobial, anti-hypertensive, antithrombotic, antimutagenic and fibrinolytic effects, as well as glucose-reducing platelet activity. It is also indicated for decreasing cholesterol and treating arteriosclerosis 12 . However, its anticoagulant effect has been proven in studies that have demonstrated a reduction in platelet activity, leading to hemorrhage 4,13 .…”
Section: Garlic (Allium Sativum)mentioning
confidence: 99%
See 1 more Smart Citation